Konsep Pernikahan Dalam Pandangan Postmodernisme: The Concept of Marriage in the View of Postmodernism - Tajuddin, M. Reivanut; Soleh, Achmad Khudori (Jurnal Filsafat Indonesia, 2024)
Postmodernism is a critique of modern society and its failure to fulfill its promises. Marriage in the view of modernism is considered to still have shortcomings that must be corrected, the view of postmodernism is generally known as the antithesis of modernism. This research aims to find out the application of the concept of marriage in the view of postmodernism. This research is a type of library research. The main source used in this research is the book Postmodernism by Akhyar Yusuf Lubis. The results obtained show that the source of postmodernism is relativism, the method used is deconstructive and anti-objective interpretation, its validity is the rejection of a single narrative, recognition of the role of power in the formation of knowledge, or understanding that meaning is contextual and can change over time. Deconstruction in the context of postmodernism refers to an analytical approach to texts and concepts that aims to discover and expose their contradictions, uncertainties and ambiguities. Marriage before the era of postmodernism was characterized by strong social structures, strong norms, and a traditional understanding of the institution of marriage. Marriage in the era of postmodernism includes: strong individualism, a break from traditional norms, a plurality of values, the importance of communication, flexibility in roles, the importance of consent and agreement.